Promouvoir l’art de la traduction parmi les lycéens. Le projet Traducteur en herbe à l’Université de Wrocław - Solová, Regina (2023)
Our contribution is part of the reflection in translation studies focused on the teaching of translation. Its objective is to take stock of the project Traducteur en herbe carried out by the Institute of Romance Studies at the University of Wrocław since 2014. Aimed at learners of the French language, the initiative focuses on the practice of translation, an activity that is absent from the secondary education curriculum in Poland. The objective of the project is to promote the art of translation among high school students and to arouse their interest in the French language and civilization. From an institutional point of view, the purpose of the event is to familiarize students with the university environment and stimulate their interest in the courses offered at the Institute. The presentation of the project is an opportunity to reflect upon the errors made by novice translators who try their hand at literary translation. It can be useful for teachers of translation, secondary school teachers and all those interested in actions aimed at awakening young people’s interest in the art of translation.
Keywords: translation practice at secondary school; university translation project for secondary schools; cooperation between the university and the secondary school; natural translator; natural translator errors; natural translator’s competences